2023
DOI: 10.1186/s40249-023-01056-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of socioeconomic status with infectious diseases mediated by lifestyle, environmental pollution and chronic comorbidities: a comprehensive evaluation based on UK Biobank

Abstract: Background Socioeconomic status (SES) inequity was recognized as a driver of some certain infectious diseases. However, few studies evaluated the association between SES and the burden of overall infections, and even fewer identified preventable mediators. This study aimed to assess the association between SES and overall infectious diseases burden, and the potential roles of factors including lifestyle, environmental pollution, chronic disease history. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Third, enhancing health education is paramount. Persistent efforts to promote personal hygiene and public awareness can signi cantly reduce transmission rates (39). Fourth, community-based interventions (40), including patriotic health campaigns and active community participation, play a pivotal role.…”
Section: Discussionmentioning
confidence: 99%
“…Third, enhancing health education is paramount. Persistent efforts to promote personal hygiene and public awareness can signi cantly reduce transmission rates (39). Fourth, community-based interventions (40), including patriotic health campaigns and active community participation, play a pivotal role.…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of females in this compared to males may be due to the fact that females themselves have higher cortisol levels than males; both smoking and drinking are the results of compensation for bad childhood behaviors ( 41 ). TDI indices tend to reflect socio-economic levels at the regional level ( 42 ), with higher scores indicating poorer areas ( 35 ), which may put pressure on parents to make children more vulnerable to ACEs. Previous research has shown that social background is an important factor influencing ACEs ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…We retrieved the following data, collected by the UK Biobank study team collected data through questionnaires at baseline: sociodemographic factors (age, sex, race, education, employment status); body mass index (BMI); lifestyle factors (smoking, alcohol consumption, physical activity); Townsend deprivation index (TDI); self-reported diseases (hypertension, diabetes, stroke, angina, and heart attack); and environmental pollutants (particulate matter with aerodynamic diameters of <2.5 μm (PM 2.5 ), and nitrogen dioxide (NO 2 )). The detailed definitions of alcohol consumption, physical activity, and environmental pollutants are described elsewhere [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%